Refurbishment and repair in construction - Doran, David (Whittles, 2009)
Annotation Provides a comprehensive manual encompassing a multitude of topics that forms an invaluable aide-memoire for practitioners and students alike. It guides the reader through the complex maze of demands to achieve a successful contract and is the perfect handy reference for newly-qualifed engineers.
Keywords: Buildings -- Repair and reconstruction.; Buildings -- Remodeling for other use.; Architecture -- Conservation and restoration.; elektronické knihy; electronic books